2014
DOI: 10.5812/numonthly.22390
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Molecular Identification of Mycoplasma Hominis in Infertile Female and Male Reproductive System

Abstract: Background:Infection of urogenital system with Mycoplasma potentially affect reproductive system and increases infants mortalities. Therefore, detection of these organisms is an important issue that should be considered and appropriate diagnostic methods should be used to identify these microorganisms. In the female reproductive system, infection can affect different parts of the cervix, endometrium, and fallopian tube. The extent of this infection in different diseases and its pathogenesis might be related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…Thirty‐five studies used PCR or culture to isolate specific bacteria, namely Chlamydia trachomatis , Ureaplasma spp. and Mycoplasma spp 9,19,51,52,55,60‐89 . The PCR technique identified C trachomatis in 15 studies with reported prevalence of between 0.3% and 43.3% in infertile men, which is in contrast to the culture technique where this species was not identified in any of the studies (0/20).…”
Section: Evidence Synthesismentioning
confidence: 88%
“…Thirty‐five studies used PCR or culture to isolate specific bacteria, namely Chlamydia trachomatis , Ureaplasma spp. and Mycoplasma spp 9,19,51,52,55,60‐89 . The PCR technique identified C trachomatis in 15 studies with reported prevalence of between 0.3% and 43.3% in infertile men, which is in contrast to the culture technique where this species was not identified in any of the studies (0/20).…”
Section: Evidence Synthesismentioning
confidence: 88%
“…In our study, in patient and control groups, 10.09% and 4.58% of women had vaginal infections, respectively. Studies showed that M. genitalium is a common causative agent of STDs in men and women and is a reason for infertility among infected people [16]. In Iran, Amirmozafari et al [17] reported that in 210 genital swabs taken from 210 patients, mycoplasma strains were isolated from 39.5% of patients using a selective mycoplasma isolation media, but using PCR 57.1% of patient samples were found to be positive for mycoplasmas.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, U. urealyticum usually causes urogenital tract infection, and it is often accompanied by M. hominis infection (Jamalizadeh et al, 2014;Lee et al, 2016;Moragianni et al, 2019). Therefore, we need to further improve the RPA-Cas12a-LFS detection system to detect M. hominis and U. urealyticum infection, such as developing a multi-detective platform combined with other Cas proteins, which is more meaningful for clinical practice.…”
Section: Discussionmentioning
confidence: 99%